Consumer Protection via Products Liability; is transformation needed? - Liyanage, Udapadie S. (My University, 2011)
The issue of consumer protection is at the centre of the discussion in the present scenario in which economies are open and a wide variety of goods and services available in the marketplace for human consumption. Primarily, consumers are vulnerable since the legal protection given to consumers against manufacturers is not strong enough. Particularly, fatal and physical injuries such as deaths, deformities, permanent disabilities and illnesses caused by defective products involve a policy issue to be considered by a jurisdiction. Secondly, it is very difficult to prove the nexus between the manufacturer of the product and the consumer at all times. Thirdly, modern rules of world trade monopolize evolving liability regimes. This is evident when analyzing the legal work of the international community on consumer rights. Still, it has only guide lines on consumer rights which have no legal effect, but merely provide an internationally recognized set of basic objectives.